The Position Of Attorney Power Of Charge Mortage Right Made By Notice With The PPAT Format Required From The Act Number 2 Of 2014 On The Position Of Notary In Pemalang City - Yusuf Ady Kurniawan; Dian Rahayu Windyastuti (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The summary of the issues in this study is 1) how is the implementation of the Authorization of Authorization of Liability in the Barriers currently under way? 2) what are the issues raised in the implementation of the current Authorization of Burden of Rights on the Barriers? 3) How should the implementation of the Authorization of the Liability of the Liability of Barriers be made? The type of research used is sociological juridical. The result of this study is that there is a disharmony between the provisions of Article 38 of the Notary Department Law and Article 96 paragraph (1) of Equity No. 8 The of 2012. The factor affecting the emergence of the question in the making of the SKMHT is that the regulatory factor is disharmonization between Article 38 of the Notary Department Law and Article 96 paragraph (1) of Civil Code. 8 of 2012,Keywords: Position; Warrant of Burden of Rights; Notary.